Mechanism of ribosome translation through mRNA secondary structures - Xie, Ping; Chen, Hong (International journal of biological sciences, 2017)
A ribosome is a macromolecular machine that is responsible for translating the genetic codes in messenger RNA (mRNA) into polypeptide chains. It has been determined that besides translating through the single-stranded region, the ribosome can also translate through the duplex region of mRNA by unwinding the duplex. To understand the mechanism of ribosome translation through the duplex, several models have been proposed to study the dynamics of mRNA unwinding. Here, we present a comprehensive review of these models and also discuss other possible models. We evaluate each model and discuss the consistency and/or inconsistency between the theoretical results that are obtained based on each model and the available experimental data, thus determining which model is the most reasonable one to describe the mRNA unwinding mechanism and dynamics of the ribosome. Moreover, a framework for future studies in this subject is provided.